WOMEN IN POWER AT THE LOCAL LEVEL - Muhtar Haboddin (KYBERNAN: Jurnal Ilmiah Ilmu Pemerintahan, 2023)
This article aims to explore the presence of women in power at the local level. The choice of this theme isvery interesting for two reasons. First, the election of regional heads directly opens women's access topower at the local level. In several regions in Indonesia, women have succeeded in becoming regents andmayors thanks to the direct election of regional heads. This phenomenon is part of the portrait ofwomen's success in the local political power struggle. Second, the positions of regents and mayors areincreasingly open to being contested in line with the strengthening of dynastic politics. This means thatdynastic political practices are increasingly enabling women to rule as regional heads. Because they arepart of the effort to maintain her husband's power. It is these two points that we want to prove throughsecondary data collection methods through critical reading of several pieces of literature that are relevantand related to writing. Meanwhile, the theory that will be used in dissecting women in power is thetheory of democracy which is interpreted as a mechanism for gaining power through competitivestruggles in elections. The choice of democratic theory is very appropriate because it substantiallycontains two things: participation and competition. Participation and competition are a must in thestruggle for the position of regent and mayor. With this way of thinking, it is believed to be able to revealin detail the involvement and ability of women in gaining power. Thus, the presence of women in powerat the local level shifts the perspective of power politics which is pro-men but gives a new meaning thatpower politics is increasingly friendly to women. The result is that women are expected to have morepower at the local level.